1951
DOI: 10.1017/s0007485300025311
|View full text |Cite
|
Sign up to set email alerts
|

The Mosquitoes of Bwamba County, Uganda VIII.—Records of Occurrence, Behaviour and Habitat

Abstract: At the time of writing, 1949, field work on mosquitoes has been carried on in Bwamba County, western Uganda, for a period of ten years, with very few intermissions. The topography and vegetation of this area have been described elsewhere (Haddow, 1945a). The main effort has centred round the search for forest vectors of yellow fever, but much work has also been done in native plantations, huts, etc. While genera such asAëdes and Taeniorhynchus have, inevitably, required special attention, records of all mosqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

1973
1973
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 15 publications
4
26
1
Order By: Relevance
“…perfuscus, which made up 50.7% of the mosquitoes collected (Table 2). This differs from previously published collection records for this area that reported that the most frequently captured species were Aedes (Stegomyia) africanus (Theobald), Mansonia (Mansonioides) africana (Theobald), and Anopheles (Celia) gambiae (Giles) (Haddow 1945b;Haddow et al 1947Haddow et al , 1951Haddow and Mahaffy 1949). However, these previous studies used human-baited collection methods that would not have attracted the nonanthropophilic Cx.…”
Section: Resultscontrasting
confidence: 77%
See 3 more Smart Citations
“…perfuscus, which made up 50.7% of the mosquitoes collected (Table 2). This differs from previously published collection records for this area that reported that the most frequently captured species were Aedes (Stegomyia) africanus (Theobald), Mansonia (Mansonioides) africana (Theobald), and Anopheles (Celia) gambiae (Giles) (Haddow 1945b;Haddow et al 1947Haddow et al , 1951Haddow and Mahaffy 1949). However, these previous studies used human-baited collection methods that would not have attracted the nonanthropophilic Cx.…”
Section: Resultscontrasting
confidence: 77%
“…In November 2008, this species made up 78.6% of the Sempaya collection, Mattingly (1957) and a more detailed description has subsequently been published by Huang (2004). Therefore, it is possible that the Aedes (Stegomyia) aegypti (L.) listed in Bundibugyo District (Bwamba County) (Haddow 1945b;Haddow et al 1947Haddow et al , 1951Haddow and Mahaffy 1949) included Ae. aegypti formosus because these subspecies are morphologically very similar and no formal description was available at the time of the collections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The capture of unfed females that have either alighted on, or are hovering around, the bait is commonly taken as showing that they have been attracted for the purpose of taking a blood-meal, but this may not always be true. Uranotaenia, Ficalbia and Hodgesia species are sometimes caught at bait (Haddow et al, 1951;Macdonald, 1957;Mattingly, 1949b), but there is often no clear evidence that they would bite if given the opportunity. In Canada, Hocking et al (1950) and Haufe (1952) recorded separately the landing and biting rates of Aedes species attracted to man, and Haddow & Ssenkubuge (1963) emphasised the importance of distinguishing between these two phenomena, i.e.…”
Section: Composition Of the Catchmentioning
confidence: 99%